Penerapan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah (SAK EMKM) Dalam Penyusunan Laporan Keuangan Pada Istiqamah Store Di Lhkosemauwe - Intan Fitri Panisa Harahap; Tuti Anggraini; Kusmilawaty Kusmilawaty (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
MSMEs have high potential for economic development, but this is not balanced by the quality of the MSMEs themselves. This can be seen from the lack of quality of recording and financial management which is not in accordance with applicable accounting standards, namely SAK EMKM. The purpose of this research is to determine the form of the Istiqamah Store financial report, to determine the application of SAK EMKM in preparing the Istiqamah Store financial report, and to determine the obstacles faced in preparing the SAK EMKM financial report. This research was conducted using qualitative methods with a descriptive approach. The location of this research was Lhoksemauwe. The data sources in this research are primary data and secondary data with data collection techniques namely observation, interviews and documentation and the data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. The results of the research show that Istiqamah Store has kept records and has prepared financial reports. The forms of financial reports made by Istiqamah Store are financial position reports and profit and loss reports. Istiqamah Store in recording and preparing financial reports is not yet in accordance with SAK EMKM, where it does not make notes to financial reports and the recognition, measurement and presentation of Istiqamah Store's financial reports is not fully in accordance with SAK EMKM. The obstacles faced are the owner's lack of knowledge of SAK EMKM, lack of human resources, not having an educational background in accounting and never having attended training related to preparing financial reports.